Coherent structures and mixing enhancement in a confined impinging-jet mixer. (23rd November 2022) - Jin, Linna; Cao, Yuhui
Highlights: The reliability of IDDES method in simulating stagnation-point flows was confirmed. Some new coherent structures were discovered with the aid of representative phases. The generation and evolution mechanisms of various coherent structures were explored. Turbulent activity and mixing quality were quantified by phase-averaging analysis. The association between coherent structures and mixing enhancement was evaluated. Abstract: This study attempted to apply improved delayed detached-eddy simulation (IDDES) method to the prediction of the turbulent mixing in a confined impinging-jet mixer (a simplified model of a side-dump combustor). It was found that the time-averaged velocity and second-order statistics were in good agreement with available experimental data, demonstrating the reliability of IDDES for the numerical study of impinging jets. We visualized all discovered coherent structures and revealed the existence of two arrays of quasi-two-dimensional spanwise vortices in the jet shear layers and the continuous rolling-up of large-scale counter-rotating spanwise vortices in the downstream region with the aid of conditional sampling method. We provided insights on the generation and evolution mechanisms of both discovered and newly-discovered coherent structures. Furthermore, the effects of coherent structures on phase-averaged turbulence statistics were evaluated. The improvements of mixing efficiency associated with coherent structures were elaborated through the phase-averaging analysis on heat flux components.